1999
DOI: 10.1074/jbc.274.36.25701
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AMP Deaminase by Phosphoinositides

Abstract: AMP deaminase (AMPD) converts AMP to IMP and is a diverse and highly regulated enzyme that is a key component of the adenylate catabolic pathway. In this report, we identify the high affinity interaction between AMPD and phosphoinositides as a mechanism for regulation of this enzyme. We demonstrate that endogenous rat brain AMPD and the human AMPD3 recombinant enzymes specifically bind inositide-based affinity probes and to mixed lipid micelles that contain phosphatidylinositol 4,5-bisphosphate. Moreover, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…It has been suggested that inositol polyphosphates may compete with phosphoinositides in the regulation of phospholipase C␦ (40), AP-2, Bruton's tyrosine kinase, synaptotagmin II (20), and AMP deaminase (reviewed in Ref. 41). Levels of InsP 6 in some cells may reach 15-60 M (37), and it is the most abundant inositol polyphosphate in most vertebrate cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that inositol polyphosphates may compete with phosphoinositides in the regulation of phospholipase C␦ (40), AP-2, Bruton's tyrosine kinase, synaptotagmin II (20), and AMP deaminase (reviewed in Ref. 41). Levels of InsP 6 in some cells may reach 15-60 M (37), and it is the most abundant inositol polyphosphate in most vertebrate cells.…”
Section: Discussionmentioning
confidence: 99%
“…A positively charged surface within the PH domain has been shown to represent the ligand binding site to phosphoinositides (45). In fact, the C-terminal region of isoform E has two putative PH domains (31), and these stretches of sequence contain 11 of the 29 histidine residues found in the AMPD3 polypeptide. Data presented in this study have shown that N-carbethoxylation of as many as 18 histidine residues in each isoform E subunit is accompanied by the near elimination of its membrane binding capacity.…”
Section: Figmentioning
confidence: 99%
“…Negative charge potentials of intracellular membranes are due, in part, to the presence of a variety of anionic phospholipids. Among these, PtdIns(4,5)P2 is a component of the cytoplasmic membrane that can interact with isoform E. PtdIns(4,5)P2 is a pure noncompetitive inhibitor of this enzyme with a K i of 110 nM (31), which may also explain the associated catalytic inhibition of membrane-bound isoform E. While other membrane-derived sources of phosphate groups could bind and inhibit this enzyme, low micromolar concentrations of neomycin are able to simultaneously relieve catalytic inhibition and disrupt the protein-lipid interaction involving isoform E. Neomycin is an aminoglycoside antibiotic with six primary amine groups that binds strongly to PtdIns(4,5)P2 in intracellular membranes (36,38,39). Although neomycin does not distinguish between PtdIns(4,5)P2 and PtdIns(3,4)P2 (39), the former is the major bisphosphate inositol in mammalian cells and therefore a more likely in vivo target for isoform E.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations